'Legitimate Knowledge': An Auto-Ethnographical Account of an African Writing Past the White Gaze in Academia. (4th May 2019) - Goitom, Mary
ABSTRACT: This article explores how issues of race and prejudice permeate knowledge production. By way of theory-driven processing, this article examines how traditional positivist practices, entrenched more than half a century ago, continue to dominate and have set the foundations by which knowledge is acquired, disseminated, understood and naturalized in two aspects: academia (tenure) and the publication process. This article further discusses how social justice and activism figure into productivity and concludes with some practical steps and suggestions to advance a more inclusive critical pedagogy in research, teaching and service.